2020
DOI: 10.1186/s42238-020-00047-9
|View full text |Cite
|
Sign up to set email alerts
|

Substance use during pregnancy: impact on Colorado community hospital

Abstract: Background Neonatal Abstinence Syndrome (NAS) leads to increased length of stay (LOS), which leads to increased healthcare costs, and can cause financial burdens for hospitals. The purpose of the study was to determine the impact of substance use by pregnant women on a Colorado (CO) community hospital after state legalization of recreational cannabis. Methods Data were gathered retrospectively through the electronic health record at an inpatient facility and described 607 mothers and 419 newborns (total N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Outra droga encontrada no trabalho foi a anfetamina, na qual o efeito sobre o feto ainda não são bem conhecidos, mas a ocorrência de alterações morfológicas e funcionais do sistema nervoso, alterações cardíacas e desenvolvimento intrauterino inadequado foram demostradas em alguns trabalhos 24,19,20,27 .…”
Section: Illicit Drugs and Pregnancyunclassified
See 1 more Smart Citation
“…Outra droga encontrada no trabalho foi a anfetamina, na qual o efeito sobre o feto ainda não são bem conhecidos, mas a ocorrência de alterações morfológicas e funcionais do sistema nervoso, alterações cardíacas e desenvolvimento intrauterino inadequado foram demostradas em alguns trabalhos 24,19,20,27 .…”
Section: Illicit Drugs and Pregnancyunclassified
“…Em relação ao tempo de internação da gestante e recém-nascido, os estudos 19,30,33 deste trabalho mostraram um aumento de 3 dias na internação, sendo necessário o uso da Unidade de Terapia Intensiva (UTI) 19 . Os recém-nascidos expostos ao cannabis, crack e cocaína necessitaram de internação em UTI por apresentarem estenose retal 16 ou outras malformações no cérebro 35 , abdomen e até mesmo a presença de fenda palatina 16 na cavidade oral do neonato.…”
Section: Illicit Drugs and Pregnancyunclassified
“…The absolute risk for severe NAS (need for pharmacologic treatment) was highest in infants co-exposed to opioids and gabapentin. Conversely, some studies showed that the risk of NAS was not affected by other psychotropic medications ( 23 25 ). It is unclear if drug-drug interactions or other factors (e.g., socioeconomic, maternal stressors, other medical or psychiatric disorders) contribute to the severity of withdrawal in infants with polysubstance exposure.…”
Section: Effects Of Polysubstance Use On the Severity Of Nasmentioning
confidence: 99%